ANOSMIA SYMPTOMS AND RT-PCR SWAB RESULTS IN COVID-19 DIAGNOSTICS - Lusida, Vincent Geraldus Enoch; Limawan, Denillia; Arifin, Fabilla Faiz; Utami, Nabilah Puspa; Kesuma, Raudhatuzzahra; Qonitatillah, Jihan; Amatullah, Nida` Fahima; Prajitno, Subur (Universitas Airlangga, 2022)
Coronavirus Disease-19 (Covid-19) is an infectious disease that has become a pandemic since March 11, 2020. PCR (Polymerase chain reaction) swab is a definitive diagnostic tool for Covid-19, because it has a high level of sensitivity and specificity. One of the symptoms of this infection is anosmia. This study aimed to determine the relationship between the symptoms of anosmia and the positive RT-PCR swab results in Covid-19 diagnostics. This study used a systematic review and meta-analysis method that was in accordance with PRISMA. From 16 articles that met the inclusion and exclusion criteria, we selected 12 articles through EPHPP that reported smell disorder among Covid-19 patients. Four reports studied whether smell disorder was independently associated with Covid-19 diagnosis. The frequency of anosmia ranged between 7,5-95%. Anosmia has high specificity for detecting Covid-19 but has low sensitivity. There was a strong relationship between anosmia symptoms and positive RT-PCR swab results. This showed that anosmia can be a marker for patients to carry out further investigations.